Andrew Johnson - Gordon-Reed, Annette. (American presidents series (Times Books (Firm)), 2011)
A portrait of America's seventeenth president describes Andrew Johnson's failed efforts to bring about reconciliation following the Civil War, the antagonism of congressional leaders who sought his impeachment, and his legacy for the present.